Community Science Education: Critical Science Literacy and Community Engagement Related to Shale Gas Development - Esther Prins; Shannon Frey (Adult Education Research Conference, 2016)
This paper examines how 48 adults in a non-formal education class on shale gas development in two rural counties expanded their scientific knowledge, developed critical science literacy, and applied what they learned in the course. The findings elucidate adults’ relationships with science and their self-perceptions as scientifically knowledgeable citizens.
Keywords: adult education; informal science learning; critical science literacy; environmental science education; natural gas development